Representasi Budaya Jawa dalam Gaya Komunikasi IShowSpeed Pada Konten Youtube “Sea Tour” Di Yogyakarta - Rini, Muninggar Setiyo; Permadi, Didi; Edy, Sarwo (P3M Politeknik Negeri Media Kreatif, 2025)
Communication style refers to the way a person interacts with others. IShowsSpeed acts as a communicator conveying messages about local cultural values. The cultural background, values, and habits from two different cultures can influence a communicator's communication style. This research aims to understand IShowSpeed's communication style in his YouTube streaming content titled